2002
DOI: 10.1002/polb.10331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of melt‐processing conditions on the quality of poly(ethylene terephthalate) montmorillonite clay nanocomposites

Abstract: Organically modified montmorillonite was synthesized with a novel 1,2-dimethyl-3-N-alkyl imidazolium salt or a typical quaternary ammonium salt as a control. Poly(ethylene terephthalate) montmorillonite clay nanocomposites were compounded via melt-blending in a corotating mini twin-screw extruder operating at 285°C. The nanocomposites were characterized with thermal analysis, X-ray diffraction, and transmission electron microscopy to determine the extent of intercalation and/or exfoliation present in the syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
180
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(188 citation statements)
references
References 7 publications
5
180
0
3
Order By: Relevance
“…However, in order to take full advantage of all these benefits, the surfactant and, subsequently, the nanocomposite, must "survive" the fabrication process or, in other words, the temperature or the extended residence time under shear must not lead to material degradation. If the processing or the synthesis temperature of the polymer exceeds the maximum temperature at which the surfactant is stable, then the latter will undergo degradation, with negative effects both on the appearance of the material and its properties [8], [9], [10], [11], [12], [13] and [14]. The most common, and commercially available, surfactants are quaternary ammonium salts, that when present as cations in montmorillonite, typically begin degradation at 200 °C or below [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, in order to take full advantage of all these benefits, the surfactant and, subsequently, the nanocomposite, must "survive" the fabrication process or, in other words, the temperature or the extended residence time under shear must not lead to material degradation. If the processing or the synthesis temperature of the polymer exceeds the maximum temperature at which the surfactant is stable, then the latter will undergo degradation, with negative effects both on the appearance of the material and its properties [8], [9], [10], [11], [12], [13] and [14]. The most common, and commercially available, surfactants are quaternary ammonium salts, that when present as cations in montmorillonite, typically begin degradation at 200 °C or below [15].…”
Section: Introductionmentioning
confidence: 99%
“…Davis et al [69] carried out a study on the silicate morphology of PET based PLSNs produced using melt mixing. Two different layered silicate surfactant modifications were tested in the process.…”
Section: Poly(ethylene Terephthalate) (Pet) Based Pls Smentioning
confidence: 99%
“…8,12,13 Ngo et al 14 and Begg et al 15 found that imidazole exhibits resistance to ring fission during thermal rearrangements of 1-alkyl-and 1-aryl-imidazoles at temperatures above 600°C, which indicates that the imidazolium cation is more thermally stable than the alkyl ammonium cation. Experimental results 8,[16][17][18][19] *Corresponding author e-mail address: meiqilin@whut.edu.cn concerning imidazolium-intercalated MMT showed an increase in thermal stability as compared to ammonium-modified MMT. He et al 20 reported that the initial decomposition temperature (temperature at 5% weight loss T 0·05 ) of 1-hexadecane-3-methylimidazolium bromine, 1-hydroxyethyl-3-hexadecane imidazolium bromine and 1,3-dihexadecane imidazolium iodine with saturated alkyl groups was higher than 250°C.…”
Section: Introductionmentioning
confidence: 99%